The translation and validation of the Postpartum Depression Screening Scale (PDSS) : towards improving screening for postpartum depression in English- and Afrikaans-speaking South African women - Maree, David J.F. (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2012.